Seizure First Aid Training For people with Epilepsy (SAFE) frequently attending emergency departments and their significant others: results of a UK multi-centre randomised controlled pilot trial. Issue 4 (16th April 2020) - Noble, Adam J; Snape, Dee; Nevitt, Sarah; Holmes, Emily A; Morgan, Myfanwy; Tudur-Smith, Catrin; Hughes, Dyfrig A; Buchanan, Mark; McVicar, Jane; MacCallum, Elizabeth; Goodacre, Steve; Ridsdale, Leone; et al.
Abstract : Objective: To determine the feasibility and optimal design of a randomised controlled trial (RCT) of Seizure First Aid Training For Epilepsy (SAFE). Design: Pilot RCT with embedded microcosting. Setting: Three English hospital emergency departments (EDs). Participants: Patients aged ≥16 with established epilepsy reporting ≥2 ED visits in the prior 12 months and their significant others (SOs). Interventions: Patients (and their SOs) were randomly allocated (1:1) to SAFE plus treatment-as-usual (TAU) or TAU alone. SAFE is a 4-hour group course. Main outcome measures: Two criteria evaluated a definitive RCT's feasibility: (1) ≥20% of eligible patients needed to be consented into the pilot trial; (2) routine data on use of ED over the 12 months postrandomisation needed securing for ≥75%. Other measures included eligibility, ease of obtaining routine data, availability of self-report ED data and comparability, SAFE's effect and intervention cost. Results: Of ED attendees with a suspected seizure, 424 (10.6%) patients were eligible; 53 (12.5%) patients and 38 SOs consented. Fifty-one patients (and 37 SOs) were randomised. Routine data on ED use at 12 months were secured for 94.1% patients. Self-report ED data were available for 66.7% patients. Patients reported more visits compared with routine data. Most (76.9%) patients randomised to SAFE received it and no related serious adverse events occurred. ED use at 12 months was lower in the SAFE+TAU arm compared with TAU alone, but not significantly (rate ratio=0.62, 95% CI 0.33 to 1.17). A definitive trial would need 674 patient participants and 39 recruitment sites. Obtaining routine data was challenging, taking 8.5 months. Conclusions: In satisfying only one predetermined 'stop/go' criterion, a definitive RCT is not feasible. The low consent rate in the pilot trial raises concerns about a definitive trial's finding's external validity and means it would be expensive to conduct. Research is required into how to optimise recruitment from the target population. Trial registration number: ISRCTN13871327